Meningkatkan Motivasi Belajar Siswa Kelas V SD Muhammadiyah Integratif Dukun Pada Proses Pembelajaran Pendidikan Kewarganegaraan dengan Metode Pembelajaran Kooperatif Tipe Jigsaw - Puspitasari, Devita Indah; Azhar, Farid Syahrul; Khasanah, Intan Aminatul; Hajron, Kun Hisnan (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the learning motivation of the SD Muhammadiyah Integrative Shaman in grade 4. This study used a collaborative classroom action research method, where the researcher acted as the executor of the action and the teacher acted to observe the process of the action. This classroom action research aims to increase the learning motivation of fifth grade students of SD Muhammadiyah Integratif Dukun. That in cycle 1 out of 10 fifth grade students in cycle 1 only 4 students or 40% meet the KKM and overall from 4 students the average score obtained of 76.25. In cycle 2 generally categorized as GOOD (in descriptive scale) as many as 1 student or 8.0% Strongly Agree, then there are 9 students or 92.00% who are categorized Agree. The increase in student learning motivation based on this is optimal because students who get scores below the Minimum Completeness Criteria (KKM) of 72 are no longer available and students who are above KKM 100% mean that Cycle 2 learning is successful or COMPLETE.